Предмет: Литература,
автор: SansTheCoolBRO
(3x^2+x)^2=
(y^2-2a)(2a+y^2)=
(2+m)^2(2-m)^2=
Помогите
Ответы
Автор ответа:
0
Ответ:
y^2-2a)(2a+y^2)=(y^2-2a)(y^2+2a)=y^4-4a^2
(3x^2+x)^2=9x^4+6x^3+x^2
(2+m)^2(2-m)^2=((2+m)(2-m))^2=(4-m^2)^2=16-8m^2+m^4
4x^2y^2-9a^4=(2xy-3a^2)(2xy+3a^2)
25a^2-(a+3)^2=(5a-a-3)(5a+a+3)=(4a-3)(6a+3)
27m^3+n^3=(3m+n)(9m^2-3mn+n^2)
Похожие вопросы
Предмет: Русский язык,
автор: sertyg1982
Предмет: Русский язык,
автор: юленька40
Предмет: Українська мова,
автор: голостан
Предмет: Математика,
автор: Lyblykotika
Предмет: Английский язык,
автор: Алевтина582